Analisis Pengaruh Konsumsi Rumah Tangga terhadap Pertumbuhan Ekonomi di Sulawesi Tenggara - Permana, Teguh; Puspitaningsih, Andriani (Ebisma (Economics, Business, Management, & Accounting Journal), 2025)
This study aims to determine the effect of household consumption on economic growth in Southeast Sulawesi Province. The research is quantitative in nature and employs a simple regression analysis. Household consumption serves as the independent variable (X₁), while economic growth is the dependent variable. The data used are secondary data obtained from the Central Statistics Agency (BPS) of Southeast Sulawesi Province for the period 2010–2024 at constant prices. The results of the study show that the t-test produced a probability value for household consumption that is smaller than the alpha value of 0.05, indicating a significant influence. The coefficient of determination (R²) of 99% demonstrates excellent model performance. Household consumption has a positive effect on real economic growth. The model estimation results indicate that an increase in household consumption will be followed by an increase in GRDP during the same period, consistent with the aggregate demand framework and the Keynesian multiplier effect.